WHY GEN Z EMPLOYEES INTEND TO LEAVE: TOXIC LEADERSHIP, ENVIRONMENT, AND SELF-AFFIRMATION IN ISLAMIC EDUCATIONAL INSTITUTIONS - Mukhtar, Afiah; Asmawiyah, Asmawiyah; Al-Anesi, Abdul Salam Hamood Ghaleb; Masradin, Masradin; Shafwah, Rif'ah (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Turnover intentions among Generation Z employees are a problem in human resource management, particularly in Islamic educational institutions. Despite upholding spiritual and ethical values, these institutions often face challenges in their implementation, such as destructive leadership and a hostile work environment. This complexity is compounded by Gen Z's sensitivity to psychological stress. Objective: This study analyzes the influence of destructive leadership and a conducive work environment on turnover intention among Gen Z employees in Islamic educational institutions, with self-affirmation as a mediator. Methods: A quantitative survey was conducted with 125 Generation Z employees working in Islamic educational institutions in Makassar. Data were analyzed using structural equation modeling. Results: Destructive leadership decreased self-affirmation, thus increasing turnover intention. However, a conducive environment increased self-affirmation but had no direct effect on turnover intention. Self-affirmation significantly mediated both relationships. Conclusion: Gen Z employees in Islamic educational institutions tend to have intentions to leave if they experience toxic leadership and an unsupportive work environment. However, strong self affirmation can mitigate these negative influences. These findings have implications for human resource management in Islamic educational institutions to provide a supportive work environment, especially for the younger generation who are more sensitive to psychological issues.